Allegorical figure of a season - Ghosh, Ayan (Jio Institute, 2023)
Flora Fountain is made from fine Portland stone, which is quarried in Dorset, England. It was designed by Richard Norman Shaw (1831–1912) and sculpted by James Forsythe. The four corners of the fountain have four allegorical female figures representing the four seasons.